Prevalence of drug-related problems in patients receiving cancer treatment - Rivera Ayma, Edith (2021)
Objective: To estimate the prevalence of drug-related problems in patients who received cancer treatment. Material and methods: Observational, prospective and descriptive study carried out at the Daniel Alcides Carrión III Hospital of EsSalud, Tacna, 2018. The population consisted of 45 patients over 18. Patients with oncological treatment were included and data were collected through the clinical pharmacy chart for pharmacotherapeutic follow-up. Results: There were 36 women (80 %) and 9 men (20 %), high frequency of breast cancer (53.30 %), prostate and ovarian cancer (6.70 %). High use of paclitaxel (14 %), gemcitabine and cyclophosphamide (9.30 %). The most frequent problems were non-compliance (2.22 to 0 %), interactions (24.44 to 13.33 %) and probability of adverse effects (93.33 % which remained constant). Conclusion: There is a high prevalence of drug-related problems in patients with cancer treatment.